Statistical optimization and batch studies on adsorption of phosphate using Al-eggshell - Yan Zhang; Hui Li; Yuyan Zhang; Fengjuan Song; Xiaoqiang Cao; Xianjun Lyu; Yan Zhang; John Crittenden (Adsorption Science & Technology)
This work provides a simple and convenient method to manufacture the sorbent of Al-eggshell. The influence of AlCl 3 concentration and pH values as well as the dosage of sorbent and their interactions on adsorption of phosphate was investigated. Therefore, Box–Behnken design coupled with response surface method was adopted to explore the empirical model for phosphate species removal. It was observed that there is an optimal point, C(AlCl 3 )(0.29 mol/l)–pH(6.12)–dosage(6.72 g/l), for the goal of maximizing phosphate species removal. The second-order polynomial model for phosphate reduction was given as Removal(%) = 96.43 +10.82X1 + 4.29X2 − 0.70X3 + 2.06X1X2 − 1.72X1X3 +8.24X2X3 − 13.10X1 2  − 17.26X2 2  − 1.72X3 2 . Contour pictures implied that the interaction between pH values and sorbent dosage was the strongest, followed by C(AlCl 3 ) versus dosage and C(AlCl 3 ) versus pH. The adsorption of phosphate data had a good agreement with the Freundlich isotherm equation at 313 and 323 K. Otherwise, Langmuir–Freundlich model described the best fitness at the temperature of 293, 298, and 303 K. The process of adsorption of phosphate on Al-eggshell fitted a pseudo-second-order kinetic equation, which indicates the exothermic reaction. In conclusion, the present work suggests Al-eggshell as an efficient and environmental friendly sorbent for phosphate species adsorption from aqueous solutions.